Incidence of Anaphylaxis Associated With Sugammadex. (May 2018) - Miyazaki, Yusuke; Sunaga, Hiroshi; Kida, Kotaro; Hobo, Shotaro; Inoue, Nobuyoshi; Muto, Masayuki; Uezono, Shoichi
Abstract : We retrospectively investigated the incidence of potential sugammadex-induced anaphylaxis at a single center in Japan over a period of 3 years. The overall incidence of intraoperative hypersensitivity reaction was 0.22% (95% confidence interval [CI], 0.17%–0.29%), and the incidence of anaphylaxis was 0.059% (95% CI, 0.032%–0.10%). The total number of patients who received sugammadex during the study period was 15, 479, and the incidence of anaphylaxis associated with sugammadex was 0.039% (n = 6; 95% CI, 0.014%–0.084%). This result implies that the incidence of sugammadex-associated anaphylaxis could be as high as that for succinylcholine or rocuronium. A prospective study, including testing for identification of cause, is necessary to confirm the exact incidence of sugammadex-induced anaphylaxis; however, the present finding calls attention to this potential.